Penguatan Kompetensi Mahasiswa Melalui Program Kunjangan Industri di PT. Victoria Care Indonesia Tbk - Arsianita Nur Fattah; Alifia Ainun Rizky; Zulfikar; Fitriana (Jurnal Ilmiah Pengabdian dan Inovasi, 2026)
The industry visit based on a mini research project has become an important component in the learning process of Business Administration students at Universitas Negeri Makassar. This program involved 126 students who visited PT Victoria Care Indonesia Tbk in Bali, a company in the cosmetics industry. The activity consisted of three main stages: preparation, implementation, and evaluation, including technical briefings, observation of the production process, presentations by industry practitioners, and discussions. Data was collected through observations, research reports, and post-activity evaluations. The findings show that this program provides contextual learning experiences, enhancing students' understanding of production systems, operational management, quality control standards, and professional work culture. Additionally, the program improved students' critical reflection skills, allowing them to link theoretical concepts with practical applications. This industry visit has proven to be an effective community engagement model, supporting the integration of theory and practice in Business Administration education.